Compact octa‐band monopole antenna with independently tuning for WWAN/LTE mobile phones. Issue 1 (January 2017) - Huang, Daiwei; Du, Zhengwei; Wang, Yan
ABSTRACT: A compact octa‐band monopole antenna with the size of 70 mm × 8 mm × 4.8 mm for WWAN/LTE mobile phones is proposed in this letter. It consists of two branches and a match circuit. The two branches radiate at the lower and higher bands, respectively. Thus, the lower and higher bands can be tuned independently. The match circuit composed of a shorting strip which is used as a distributed inductance and a lumped capacitance of 3 pF that can make the lower band matched and enhance the bandwidth. The fascinating merits of the proposed antenna are that the lower and higher bands can be tuned independently and the non‐ground portion height is only 8 mm. A prototype is manufactured and measured. The measured −6 dB impedance bandwidths are 313 MHz (0.697–1.01 GHz) and 1.66 GHz (1.59–3.25 GHz) at the lower and higher bands, respectively, which can cover the LTE700, GSM850, GSM900, GSM1800, GSM1900, UMTS, LTE2300, and LTE2500 bands. The measured radiation patterns, gain, and efficiency are presented. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 59:208–214, 2017